Corn starch acid hydrolysis at the onset gelatinization temperature: Morphology, crystallinity, viscoelasticity, and thermal properties. Issue 7 (7th January 2014) - Hernández‐Jaimes, Carmen; Utrilla‐Coello, Rubi G.; Carrillo‐Navas, Hector; García‐Márquez, Eristeo; Meraz, Monica; Bello‐Pérez, Luis A.; Vernon‐Carter, Eduardo J.; Alvarez‐Ramirez, Jose
<x xml:space="preserve">Abstract</x> The evolution of acid hydrolysis (sulfuric acid 3.16 M) at the onset gelatinization temperature (57.73 ± 0.72°C) of native corn starch was monitored. A first‐order kinetics fitting was used to estimate the mean hydrolysis time (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghnnqjfrk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />τH=29.26±3.86 min</alternatives>) and maximum conversion <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghnnqjfgf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(X∞=96.62±2.70%)</alternatives>. Amylose content presented a sharp decrement of about 90% in the first 30 min. XRD results indicated A‐type to B‐type crystallinity transition in the first 10 min, with maximum crystallinity increase of about 14% after 30 min. SEM micrographs showed that hydrolysis disrupted granule morphology from regular oval‐like shape to irregular geometries with aggregation of small‐size debris. Granule size distribution broadened as hydrolysis proceeded due to fragmentation‐adhesion phenomena of eroded starch granules. Fast changes in the thermal effects during the first minutes were caused by molecular rearrangements due to fast hydrolysis of amylose in the amorphous regions. Steady shear rate and oscillatory tests showed a sharp viscoelasticity decrease caused by amylose degradation.